A curriculum for action in the community and intercultural citizenship in higher education - Porto, Melina (2015)
The purpose of the project described here is to demonstrate how the introduction of subject matter and principles from citizenship education into foreign language education combines objectives from both in order to give meaning to language education on the one hand and extend citizenship education beyond a focus on the local and the national on the other. In doing so, the educational aims of foreign language teaching - as well as its instrumental purposes - can be met and the scope of citizenship education is extended to include intercultural citizenship. The project was located in Higher Education in Argentina, where 76 students were learning English, and in Britain, where 23 students were learning Spanish. It focused on human rights violations during the football World Cup that took place in Argentina in 1978 during a period of military dictatorship and it was carried out in 2013 during a fourth-month period. Data were collected then and comprise documentary data (posters, PowerPoints, videos, etc.) and conversational data (online communication between the Argentinian and British students using Skype). This article describes the processes of the project and the ways in which students reacted, particularly the Argentinian students who felt personally involved, and demonstrates how the combination of language and citizenship education, when given the additional viewpoint of an insider and outsider perspective, leads to significant developments in learners' lives: an identification with a transnational group and perspective, and a willingness to become directly and critically involved in action in the community.